Global perspectives on nationalism
1 online resource (x, 333 pages).
Keywords: "Global Perspectives on Nationalism takes an interdisciplinary approach informed by recent theorisations of nationalism to examine perennial questions on the topic. The idea of nationalism centres on questions of ethnicity, culture, religion, language, and access to resources. What determines consciousness of nationalism? How is nationalism manifested, shaped, or countered through literary and cultural productions? The contributors highlight topical areas in studies of nationalism including ecology, natural resources, sustainability, globalisation, the Anthropocene, postcolonialism, indigeneity, folklore, popular culture, and queer theory. They develop innovative perspectives on nationalism through in-depth analyses of the theoretical, political, literary, linguistic, cultural, and ecological dimensions of nationalism in Argentina, Australia, Bangladesh, Bosnia and Herzegovina, China, Germany, Greece, India, Indonesia, Lebanon, Nepal, Nigeria, Poland, Scotland, Turkey, the United States, and elsewhere. This volume underscores the importance of generative dialogue between disciplines in assessing the implications of nationalism for everyday life through five thematic sections: (I) Ethnicity, Ideology, and Narration; (II) Religion, Identity, and Heritage; (III) Linguistics, Tradition, and Modernism; (IV) Music, Lyricism, and Poetics; and (V) Ecology, Environment, and Non-Human Lives. This book will be of particular value to students and researchers in philosophy, literary studies, and political theory with interests spanning ecology, ethnicity, folklore, gender, heritage, identity, linguistics, nationalism, nationhood, religion, and sexuality"--